Buku Saku Digital Bermuatan IDEAL Problem Solving Berbasis Ethnomatematika Terhadap Kemampuan Pemecahan Masalah - Eka Putri Ayuningsih; Muhamad Firdaus; Yudi Darma (J-PiMat : Jurnal Pendidikan Matematika, 2023)
Abstract. This study aims to produce learning media in the form of android applications that achieve valid, practical and effective criteria so that they are suitable for use. This research uses Research And Development (R&D) methodology. The steps for developing this application are using a 4D model but only done up to 3D which stands for define, design, develop. The subjects in this study were 19 students of class VII MTs AL Mustaqim. The instruments used in this study were media and material expert validation sheets, student and teacher response questionnaires, and a posttest.The research results related to the validity of reaching the level of validity with the category of "very valid" with the validity of the media reaching 92.82% and the validity of the material reaching 93.63%, reaching the level of practicality with the criteria of "very practical" is shown by the student response questionnaire which achieved a score of 93, 74% and the response questionnaire given by the teacher reached a score of 93.7%, achieving a level of effectiveness with the criteria of "very effective" based on the completeness score determined by the school with test results showing the percentage of completeness of students getting a score of 84.21%. With this it can be concluded that digital pocket book media containing IDEAL problem solving based on Ethnomatematics for problem solving skills in social arithmetic material is very appropriate to use.Keyword: social arithmetic, digital pocket book, IDEAL Problem Solving, Ethnomatematics, Problem Solving Ability.Abstrak. Penelitian ini bertujuan untuk membuat bahan pembelajaran dalam bentuk aplikasi Android yang memenuhi kriteria validitas, kepraktisan dan efektivitas sesuai kebutuhan pengguna. Penelitian ini menggunakan metodologi Research and Development (R&D). Tahapan pengembangan aplikasi ini menggunakan pemodelan 4D namun hanya dilakukan secara 3D yaitu singkatan dari Define, Design, Develop. Subyek penelitian proyek ini adalah 19 siswa kelas VII sekolah MTs AL Mustaqim. Alat yang digunakan dalam penelitian ini adalah lembar validasi ahli materi dan media, angket tanggapan siswa dan guru, serta post-test. Hasil penelitian terkait nilai mencapai taraf nilai “sangat autentik” dengan nilai komunikasi mencapai 92,82% dan nilai materi mencapai 93,63% mencapai taraf nilai praktis dengan kriteria “sangat realistis” menurut masukan siswa. Daftar pertanyaan. mencapai skor 93, 74 lembar jawaban yang diberikan guru mencapai skor 93,7%, mencapai tingkat keefektifan dengan kriteria “sangat efektif” berdasarkan skor ketuntasan yang ditentukan sekolah dengan hasil tes. tingkat ketuntasan tes siswa mencapai 84,21%. Dengan demikian dapat disimpulkan bahwa media digital saku yang berisi metode pemecahan masalah IDEAL berbasis ethnomatematika untuk penyelesaian masalah bidang aritmatika sosial sangat layak digunakan.Kata Kunci: aritmatika sosial, buku saku digital, IDEAL Problem Solving, Ethnomatematika, Kemampuan Pemecahan Masalah.